Os autismos na clínica nodal - Brenda Rodrigues da Costa Neves (2018)
In this study, we restricted the term autism to place a child that is not related to the social bond, manifesting an active refusal to invest in those who are in parental function, not being involved with gestures, speech and body movements in the games that are proposed, inventing their activities to an extension use of empirical objects. Anchored in the articulations between language and topology, present in Lacan's theorization, as modalizations in which the subject differentiates, composing his psychic reality, we investigate the conditions of the bond between the Royal, Symbolic and Imaginary dit-mansions, and what presents as being concerning the clinical type autism, evidencing its attempt to construct an autistic border that modalizes the enjoyment through the use: of the autistic objects, in the double and in the island of competence. We note the insinuation of a temporal logic and a specific spatiality that insisted on being present, requiring the articulation of time to the cut and surface to topology, combining such figuration of time and space in the specificity of the autistic subject, questioning what could to be the passage of the Real, which shows itself to an excessive extent in autism, through the interstices of the Symbolic and the Imaginary. We start with the hypothesis that a topological reading of the enameling mode of the three ditmansions R, S and I can provide us with the elements to locate the psychic constitution of the autistic subject. To approach the autistic from psychoanalysis implies distinguishing the clinical type of autism from apparently autistic manifestations and, in attempting to make such a distinction, link the theoretical elaborations with the presentation of clinical cases. With the non-extraction of the object a, we hypothesize that the autistic is in constant psychic work, and lacks a reading that frees his acts, which can be taken as written. Thus, instead of taking the manifestation of the autistic child as automatic, reflex or isolated in watertight signs without concatenation, we understand that their acts carry a singular invention to deal with what makes them otherness, treating the anguish, construct an autistic border that entails a subjective logic that lacks the recognition and franking of the analyst, considering it as a writing to be read. In this way, the autistic could stand back in front of the Other, but at the same time, open to make an entrance into the social bond